CDnet 2014: An Expanded Change Detection Benchmark Dataset - Yi Wang; Jodoin, Pierre-Marc; Porikli, Fatih; Konrad, Janusz; Benezeth, Yannick; Ishwar, Prakash (IEEE Computer Society Conference on Computer Vision and Pattern Recognition workshops, 2014)
Change detection is one of the most important lowlevel tasks in video analytics. In 2012, we introduced the changedetection.net (CDnet) benchmark, a video dataset devoted to the evalaution of change and motion detection approaches. Here, we present the latest release of the CDnet dataset, which includes 22 additional videos (70; 000 pixel-wise annotated frames) spanning 5 new categories that incorporate challenges encountered in many surveillance settings. We describe these categories in detail and provide an overview of the results of more than a dozen methods submitted to the IEEE Change DetectionWorkshop 2014. We highlight strengths and weaknesses of these methods and identify remaining issues in change detection.